2012
DOI: 10.4208/cicp.121209.050111s
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Continuation of Resonances and Bound States in Coupled Channel Schrödinger Equations

Abstract: In this contribution, we introduce numerical continuation methods and bifurcation theory, techniques which find their roots in the study of dynamical systems, to the problem of tracing the parameter dependence of bound and resonant states of the quantum mechanical Schrödinger equation. We extend previous work on the subject [1] to systems of coupled equations. Bound and resonant states of the Schrödinger equation can be determined through the poles of the S-matrix, a quantity that can be derived from the asymp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…In [19] it is shown that this procedure does not introduce false solutions, that is, the zeros of F are precisely the poles of S, and that it eliminates any singularities at k = 0. This is an extension of a similar result for the one-dimensional, singlechannel systems case [17,21].…”
Section: A the Case Of N Channels Equal Thresholdsmentioning
confidence: 99%
See 1 more Smart Citation
“…In [19] it is shown that this procedure does not introduce false solutions, that is, the zeros of F are precisely the poles of S, and that it eliminates any singularities at k = 0. This is an extension of a similar result for the one-dimensional, singlechannel systems case [17,21].…”
Section: A the Case Of N Channels Equal Thresholdsmentioning
confidence: 99%
“…In [19] the method has been extended to many-channel problems where all channels have the same asymptotic energy threshold. Applications have demonstrated the viability of the approach in tracing the parameter dependence of the resonance in the system.…”
Section: Introductionmentioning
confidence: 99%